2010
DOI: 10.1016/j.bej.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Production of triacylglycerols rich in palmitic acid at sn-2 position by lipase-catalyzed acidolysis

Abstract: This paper studies the synthesis of triacylglycerols (TAGs) rich in palmitic acid (PA) at sn-2 position from palm stearin (PS), a vegetable oil highly rich in PA (60%, but only 12.8% of this is located at sn-2 position). These PA rich TAGs were obtained by lipasecatalyzed acidolysis of this oil with free fatty acids (FFAs) highly rich in PA, such as commercial PA (98% PA) and a FFA extract obtained by saponification of PS (60% PA). PA has a melting point of 63 ºC and during the acidolysis reaction the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 39 publications
(27 reference statements)
0
19
0
1
Order By: Relevance
“…Other lipases, e.g., from Candida rugosa 51, Candida parapsilosis 52, R. oryzae 53, 54, Bacillus stearothermophilus 55, Mucor circinelloides (formerly Mucor javanicus 56, Fusarium heterosporum 53, Alcaligenes sp. 57 have also been verified and many of these enzymes are commercially available in free and immobilized form.…”
Section: Enzymatic Production Of Hmfsmentioning
confidence: 91%
See 1 more Smart Citation
“…Other lipases, e.g., from Candida rugosa 51, Candida parapsilosis 52, R. oryzae 53, 54, Bacillus stearothermophilus 55, Mucor circinelloides (formerly Mucor javanicus 56, Fusarium heterosporum 53, Alcaligenes sp. 57 have also been verified and many of these enzymes are commercially available in free and immobilized form.…”
Section: Enzymatic Production Of Hmfsmentioning
confidence: 91%
“…As reported in a several publications, the packed bed reactor is more suitable for industrial‐scale production, in contrast to a stirred‐tank reactor. Very few studies using the one‐step enzymatic process were reported using packed bed reactors for the production of HMFS in laboratory‐scale 57, 69, 95, 98–100. Nielsen et al 69 developed a pilot packed bed reactor on a kg scale using a mixture of lard and soybean oil FAs.…”
Section: Enzymatic Production Of Hmfsmentioning
confidence: 99%
“…The procedure was carried out at 65°C. TAG were separated by decantation of the oily phase formed after adding the hydroalcoholic solution of KOH .…”
Section: Methodsmentioning
confidence: 99%
“…This result indicates that in both reactors the kinetic of reaction is controlled by the enzymatic reaction or that the mass transfer rate when lipase is confined in the cartridge and when lipase is dispersed are similar. In previous works it was observed that reaction rates of lipase catalyzed reactions (acidolysis and alcoholysis) decreased when they were carried out with the lipase contained in packed bed reactors (Camacho et al, 2007;Esteban et al, 2009;Jiménez et al, 2010b), and it was demonstrated that at high substrate concentrations (high viscosities) the reaction rate was controlled by the mass transfer rate (Camacho et al, 2007). In this respect, the STR with the lipase contained in a cartridge filter behaves as an STR with dispersed lipase, with the advantage of maintaining the lipase in the cartridge filter.…”
Section: Influence Of Ffa (Oa)/tag Molar Ratio and Oa Puritymentioning
confidence: 98%